Peter Warlock: The composer - Collins, Brian (Cambridge Scolar Pr, 1996)
Peter Warlock is one of the several pseudonyms adopted by the critic, researcher, editor and composer, Phillip Heseltine (1894-1930). Previous studies of Warlock have almost all been exclusively biographical, using the pseudonyms as evidence of a split personality and applying this and the other controversial aspects of his life-style to an evaluation of his music. Brian Collins's analysis of Warlock's work focuses on the key elements of Warlock"s compositional tecchniques and demonstrates that the early songs, often tonally adventurous and heavily influenced by Delius and van Dierden, are natural precursors to the more familiar later style. This proved more suited to the comtemplative and philosophical songs that make up the majority of his output. In analysing Warlock's choice of subject matter and the respect he accorded to the natural stresses of the texts he used, Brian Collins offers insights into the composer's motivations and acheivements. As such his book provides reading for anyone concerned with the evolution of British music in the early part of this century.